AUDIT SISTEM INFORMASI MENGGUNAKAN STANDAR KERANGKA KERJA COBIT 5.0 DI RUMAH SAKIT - Wide Mulyana; Santi Sawitri; Mauli Dia Syahara (Department of Information System Muhammadiyah University of Riau, 2021)
Hospital is a place where health facilities are located to support the services of the sick. Each hospital usually has services in the form of registration, pharmacy to cashier. In this study, the audit was carried out using the COBIT 5.0 (Control Objective For Information and Related Technology) framework standard which is a framework created by ISACA (Information System Audit and Control Association) and ITGI (Governance Institute) in 1992 which is a standard information technology controls that have been applied internationally. COBIT 5.0 has 5 Domains, namely EDM (Evaluate, Direct And Monitor), APO (Align, Plan and Support), BAI (Build, Acquire and Implement) DSS (Deliver, Service and Support) and MEA (Monitor, Evaluate And Assess). But in this study only focuses on the use of the APO domain only. This study resulted in the maturity value of the maturity level system with a maturity level value of 2.6 which is included in level 2, namely managed process. That is, the process at this level is implemented into a process setting (planned, monitored, evaluated) and the work products of the process are implemented, controlled and maintained appropriately. Measures the extent to which work products are produced by a well-regulated process.